Ecological implications of grass bud bank and tiller dynamics in mixed-grass prairie - Ott, Jacqueline P (Kansas State University, 2014)
Perennial grass populations propagate vegetatively via the belowground bud bank. Climate, photosynthetic pathway, and growth form impact bud production, longevity, and dormancy; leading to alterations in bud bank and tiller dynamics. Previous research in mesic C₄-dominated tallgrass prairie revealed that a C₄ grass had greater bud longevity and differing bud bank dynamics than a C₃ species. This study examined the bud bank dynamics of rhizomatous and caespitose grasses in a more arid C₃ dominated prairie to gain insights into how bud banks differ among grass species, growth forms, and environments, and the relationship between bud bank characteristics and grass architecture and growth patterns. The bud bank and tiller dynamics of four perennial grasses in the C₃-dominated northern mixed grass prairie were examined over 15 months. The C₃ caespitose and rhizomatous grasses produced similar numbers of buds per tiller and their bud longevity was [greater than or equal to] 2 years. Tiller longevity drove the turnover within the bud bank of the dominant C₃ caespitose grasses Hesperostipa comata and Nassella viridula. Their polycyclic tillers (tillers that lived for more than one year) created multi-aged bud banks. The rhizomatous C₃ grass Pascopyrum smithii also had a multi-aged bud bank because buds were able to live longer than its annual tillers. Differences between caespitose and rhizomatous C₃ grass bud banks were driven by differences in tiller and rhizome production and spatial distribution. Responses to water availability fluctuations are likely buffered by the maintenance of polycyclic tillers in the caespitose grasses and flexible timing of annual tiller recruitment in the rhizomatous grass. The C₄ rhizomatous grass Andropogon gerardii had similar phenology to populations in its tallgrass prairie range center. Despite declines in bud production per tiller and lowered flowering probability in mixed-grass prairie, A. gerardii maintained a multi-aged bud bank and a positive population growth rate via vegetative reproduction at both the center and edge of its range. Bud bank dynamics of different growth forms and photosynthetic pathways, as they offer insight into the control of grass population dynamics and production, will enhance understanding of the mechanisms by which management practices and environmental change can alter perennial grasslands.
Keywords: Bud bank; Tiller dynamics; Vegetative reproduction; Grass; Mixed-grass prairie; Perennial grass; Ecology (0329); Plant Biology (0309)